Management of frailty at individual level - clinical management: Systematic literature review - Veninšek Gregor; Gabrovec Branko (Sciendo, 2018)
To deliver quality management of a frail individual, a clinician should understand the concept of frailty, be aware of its epidemiology and be able to screen for frailty and assess it when it is present, and, finally, to recommend successful interventions.